2021
DOI: 10.3390/cancers13194923
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Intratumor Heterogeneity on Consensus Molecular Subtype (CMS) in Colorectal Cancer

Abstract: The implications of intratumor heterogeneity on the four consensus molecular subtypes (CMS) of colorectal cancer (CRC) are not well known. Here, we use single-cell RNA sequencing (scRNASeq) to build an algorithm to assign CMS classification to individual cells, which we use to explore the distributions of CMSs in tumor and non-tumor cells. A dataset of colorectal tumors with bulk RNAseq (n = 3232) was used to identify CMS specific-marker gene sets. These gene sets were then applied to a discovery dataset of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 83 publications
5
22
0
Order By: Relevance
“…Recently, several studies applied scRNA-seq on CRC samples to further reveal the diversity of and the dynamic relationships between cellular components of CRC tumors and their TME 7,9,[12][13][14] . These analyses disclosed CMS features at the individual tumor cell level and stressed the high prevalence of multiple CMS phenotypes in the same patient 7,9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies applied scRNA-seq on CRC samples to further reveal the diversity of and the dynamic relationships between cellular components of CRC tumors and their TME 7,9,[12][13][14] . These analyses disclosed CMS features at the individual tumor cell level and stressed the high prevalence of multiple CMS phenotypes in the same patient 7,9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the differential content in stromal and immune cells, CRC tumors also showed ITH at the level of epithelial cells. Indeed, a variety of CMS-like signatures were detected inside each tumor sample, as previously described 30 , 42 . As expected, the mesenchymal subtype CMS4 showed the lowest epithelial ITH, while CMS3 tumors harbored the highest levels of each CMS-like cell.…”
Section: Discussionmentioning
confidence: 95%
“…This is in agreement with highly mutated tumors harboring more immunogenic mutations and consequently attracting more immune-cell infiltrates 31 . In fact, a recent study suggests that the CMS1 and CMS4 signal is mostly derived from immune and stromal cells, respectively 42 , with little contribution from tumor epithelial cells. Besides the differential content in stromal and immune cells, CRC tumors also showed ITH at the level of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the promise of using molecular subtyping to achieve precision oncology is currently more achievable today than at any time in the past, significant obstacles still remain. While the idea of molecular subtyping was created to address the problem of inter-tumor heterogeneity, advances in single cell sequencing have revealed that intra-tumor heterogeneity is another major issue to be addressed [83][84][85]. Intra-tumor heterogeneity is particularly challenging with transcriptomic measurements, where contribution from non-tumor stroma and immune cells can confound analysis of tumor intrinsic transcription and also increase risk of spatial sampling bias [86].…”
Section: Current Challenges and Potential Solutions For Ai In Molecular Subtyping And Precision Oncologymentioning
confidence: 99%